Developing an Effective Employee Selection Model to Improve Company Performance at PT. Citra Niaga Abadi - Ahyat, Muhamad; Hamdi, Nizar (Journal of Management, 2025)
This study aims to develop and analyze an effective employee selection model and its effect on company performance, by considering the role of employee suitability as a moderating variable. This study uses quantitative methods with linear regression techniques to test the relationship between the Employee Selection Model, Employee Suitability, and Company Performance. The results of the analysis show that the Employee Selection Model has a significant effect on Employee Suitability (B = 0.581, t = 10.289, sig. = 0.000) with a coefficient of determination (R² = 0.519). After adding the moderation variable, it was found that the Employee Selection Model and Employee Suitability together have a significant effect on Company Performance (F = 32.548, sig. = 0.000), although the coefficient of determination has decreased (R² = 0.402).The conclusion of this study is that the Employee Selection Model has a major role in improving Company Performance, both directly and with the moderation of Employee Suitability. However, the impact of Employee Suitability on Company Performance is smaller than that of the Employee Selection Model. Therefore, companies need to focus more on developing a competency-based selection system to ensure that recruited employees have the abilities and characteristics that match the needs of the organization.